2021
DOI: 10.3389/fphys.2021.669355
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the Oral Microbiota During a Four-Week Commercial Saturation Dive to 200 Meters

Abstract: During commercial saturation diving, divers live and work under hyperbaric and hyperoxic conditions. The myriads of bacteria that live in and on the human body must adjust to the resultant hyperbaric stress. In this study, we examined the shifts in bacterial content in the oral cavity of saturation divers, using a metagenomic approach to determine the diversity in the composition of bacterial phyla and genera in saliva from 23 male divers before, during, and immediately after 4 weeks of commercial heliox satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…The predicted changes in oxygen-dependent metabolism are consistent with the results from our prior taxonomic analysis, where the composition of bacterial communities was found to shift during the bottom phase in favor of aerobes (Proteobacteria and Actinobacteria) over anaerobes (Fusobacteria) (Monnoyer et al, 2021). An increase in pathways involved in the TCA cycle and electron carrier biosynthesis is consistent with communities in which aerobes predominate.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The predicted changes in oxygen-dependent metabolism are consistent with the results from our prior taxonomic analysis, where the composition of bacterial communities was found to shift during the bottom phase in favor of aerobes (Proteobacteria and Actinobacteria) over anaerobes (Fusobacteria) (Monnoyer et al, 2021). An increase in pathways involved in the TCA cycle and electron carrier biosynthesis is consistent with communities in which aerobes predominate.…”
Section: Discussionsupporting
confidence: 87%
“…In light of emerging awareness of the intimate interactions between the human body and its microbiota, the results may contribute to a better understanding of physiological responses to the extreme environments in saturation diving. We used PICRUSt2 for functional abundance analysis on 16S rRNA sequence data from a previous study (Monnoyer et al, 2021) and confirmed our hypothesis of a relative increase in the abundance of aerobic pathways and a concomitant decrease in anaerobic pathways. Interestingly, the analysis also predicted decreases in several components of vitB 12 biosynthesis.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations